Influence of frictional heat spread pattern on the formation of intermetallic layers at the dissimilar FSW joint interface between AA 5083 and HSLA steel. (November 2022) - Sahu, Mrinal; Paul, Atanu; Ganguly, Subhas
Abstract: The dissimilar weld interface for the AA5083 and HSLA steel alloy pair made by FSW technique was investigated to explore the impact of the friction heat flow across the thickness on the types and nature of IMC layer. The detail transmission electron microscopy (TEM) and atom probe tomography (APT) were performed to characterize the IMCs at different layer thicknesses and compositional mixing patterns of the interface. Also, a 3D moving heat source thermomechanical model was developed to simulate the FSW joining of Fe/Al alloy pair and explored the existence of heat flow pattern along the sheet thickness. The detail analysis of SAED pattern obtained from TEM bright field images was conducted to characterize the presence of types and nature of IMCs at different layer thicknesses. In this study the proximity histogram data from APT were investigated for further confirmation of existence of observed Fe/Al IMCs and atomic mixing pattern at the interface. The study identified the presence of Fe2 Al9, Fe4 Al13 and FeAl6 which are distinctly distributed over the thickness. The relative richness of Fe and Al in these IMCs are found significantly influenced by the thermal gradient in turn typically control their distribution over thickness. The Al rich IMCs such as FeAl6, possessing large ΔGf and low activation energy, found away from the frictional surface of heat source. While Fe rich IMCs form with relatively lesser ΔGf and higher activation energies are seen near the frictional surface of heat source.